Cost and uptake of income-based tax incentives for R&D and innovation - Appelt, Silvia (OECD Science, Technology and Industry Working Papers, 2023)
Despite the increasing adoption of income-based tax incentives for R&D and innovation in the OECD area and beyond, evidence on the availability, design, generosity and actual cost of these incentives remains scarce. This report helps fill this gap by documenting government efforts to provide preferential tax treatment of economic outputs of innovation activities. Drawing on the responses of national contact points to the OECD KNOWINTAX surveys carried out in 2020 and 2021, it presents new evidence on the cost (foregone tax revenues) and uptake of income-based-tax incentives by businesses in 2019, and tracks their distribution by firm size and industry and their evolution over the 2000-2019 period